Jurnalisme Lingkungan dalam Pemberitaan Wisata Taman Hutan Mangrove di Kampung Sejahtera Kota Bengkulu - Wardani, Indriati Triea; Adhrianti, Lisa; Perdana, Dionni Ditya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Environmental conditions around the world today face significant challenges and changes such as climate change, loss of biodiversity, environmental pollution, and water crisis. This study aims to find out how the news of mangrove forest park tourism in the prosperous urban village of Bengkulu on Radar media Bengkulu.diwsay.id and Mongabay.co.id .  This study used descriptive qualitative research using Zhongdang Pan and Gerald M's model framing analysis methods. Kosicki has four analysis blades: syntax, script, thematic, and rhetorical. Data collection techniques use primary data and secondary data. The research was conducted via online news text observation on the media radarbengkulu.disway.id and mongabay.co.id with 1 news on each media portal. Based on the data found, the comparison of the discrepancies in the information that emerged from the media mongabay.co.id and radarbengkulu.disway.id is often seen in the way of presenting facts and selecting sources